PROTECTION OF AN EARTHEN-ARCHAEOLOGICAL SITE: A COLLABORATIVE EFFORT BETWEEN COMMUNITY AND EXPERTS, CHILE - Bahamondez Prieto, Mónica; Muñoz González, Eduardo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The prehistoric village, Tulor 1, is located about 10 km southwest of San Pedro of Atacama in northern Chile. It is the oldest sedentary archaeological site in northern Chile, whose chronology dates back to 2250 years ago. It was excavated by archaeologists from 1981-1985. At that time, it was clear that the site was undergoing an accelerated process of deterioration, resulting from the advance of a large dune that originally covered it that currently was in the process of withdrawal. Studies were made to ind a solution to the natural processes of destruction affecting the site, and it was concluded that the active and irreversible damage is caused by the condition of the environment in which it is located. Research has shown that the best way to preserve the site was to keep it in a “buried” state. In order for that to be achieved, it was necessary to stabilize the top of the earthen walls, which had been irreversibly degraded, by designing “capping” solutions and binding based on satisfactory studies with more than 20 years of permanence. Moreover, the study of the grain size of the dragged material allowed determining of the minimum particle size necessary to cover the site with a thin layer of sand with similar features, preventing it from being carried away by the winds forecasted by the weather station installed in situ. In addition, and because it is a site whose management and care is in the hands of a small indigenous community, it was necessary to raise awareness of the site’s fragility, and to provide technical training for indigenous community to be able to perform the work of supervision and future maintenance.